University Social Responsibility (USR): Principles for a sustainable, cooperative and democratic university from the participative diagnosis of its student body - Martínez-Usarralde, María-Jesús; Lloret-Catalá, Carmen; Mas-Gil, Sara (Education Policy Analysis Archives, 2017)
The present study analyses the speech of the University under which it is recognized the presence of “University Social Responsibility” by questioning one of its participants, the student body. The objective of this research is to provide relevant conclusions to its vision and raise them to the university´s policy-makers. A methodological quantitative and qualitative systematized research was done in the course of two academic years involving 206 Social Education´ students at the University of Valencia (Spain). The study´s goal has been to carry out a participatory diagnosis on the situation of the USR and Sustainable Development based on Vallaeys, De la Cruz and Sasia questionnaire (2008). Among the results it is necessary to emphasize that the students perceive that the university provides them an ethics and citizenship training that enables them to be socially responsible individuals. However they perceive that the value-based policies should be addressed in a more coordinated and cross-cutting approach.